Lifelong Learning in Multi-Purpose Activity of Self-Employed and Employed Persons - Natalia A. Lyz; Elena V. Gladkaya (National Research Mordova State University, 2024)
Introduction. Managing the lifelong learning environment requires a certain understanding of the educational needs and demands of learners of different categories. However, there is not enough research devoted to the psychological aspects of non-formal and informal learning of working subjects. The aim of the study is to characterize the main forms of learning, inducing and sustaining motivation, engagement and self-regulation of learning among employed and self-employed individuals. Materials and Methods. The study used the methods of theoretical analysis of the problem, testing and survey with the use of educational experience diagnostics methodology and author's questionnaires based on the Informal Learning Questionnaire and Academic Motivation Scale. The empirical sampling encompassed 295 people, including 143 self-employed and 152 employed. Results. The results showed the diversity of forms of lifelong learning used by employed persons, as well as the polymotivated nature of this activity. It was found that professional and cognitive motives are the most pronounced among the employed and self-employed. Respondents are motivated to learning by the desire for self-improvement, professional development objectives, interest in the subject of training, the need for new knowledge and skills. It is proved that self-employed persons, compared to employed persons, have a higher level of involvement, self-regulation of learning and intrinsic motivation focused on professional and personal growth and diverse interests. Discussion and Conclusion. The results of the study expand scientific ideas about lifelong learning and for the first time demonstrate the specificity of involvement and motivation for learning individuals with different employment status. The materials of the article will be useful for researchers, specialists in human resources development, marketers of the education segment, and developers of additional educational programs.